Življenjski ciklus v vernakularni arhitekturi - Zupančič, Domen (AR. Arhitektura, raziskave, 2004)
A house is a cell for living; it isn't a prison cell but a cell in the biological sense, meaning optimised living, consumption of resources, quality corresponding to available circumstances, external resilience and representation. A value system cannot develop by force; participation by professions and the public is necessary. The architect is an expert, whose duty is to connect various actors in the planning process and balance all factors with respect for carefully formulated former experiences. Understanding of a system's dynamics is the core of economics and vernacular building is the answer to process dynamics. The difference between vernacular and economic is that the economic can be proved mathematically, while vernacular relies on chronological checking. Mistakes and inconsistencies are part of any system. The denser the system is with data, the lesser is the darkspot. In an indeterminable system vernacular architecture relies on its site. The measure of survival in a cultural landscape is living according to possibilities offered by the environment and knowledge. Time is included as a factor; a generation has to live in a manner that will support life of its offspring. However, despite traditions and rules of building, materials and lists of values, architecture always emerges uniquely. The apparently adamant oneness changes slowly.
Keywords: architecture; arhitektura; ljudska arhitektura; urejanje prostora; vernakularna arhitektura; vrednote; raziskave